A Multistage Support Vector Machine Based Intrusion Detection System in MANET - Pourghassem, Arvin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
Mobile Ad Hoc Networks (MANETs) have been applied in many different fields in recent years. Although MANETs are highly vulnerable to malicious behavior, complete security is complicated to achieve. Due to the insufficiency of prevention techniques, the Intrusion Detection System (IDS), which monitors system activity and detects intrusions, is generally used with other security measures. Denial of Service (DoS) type attacks such as flooding, blackhole, and grayhole attacks are acute types of network intrusion that aim to make computer/network resources unavailable to legitimate users. Intrusion Detection (ID) is a security management system that serves as an alarm mechanism for any computer network such as MANET. It detects the incoming security threats to a network and then issues an alarm message to an entity to take needed actions against the intrusion. An IDS gathers and examines information from numerous areas within a computer or a network to identify possible security breaches, including intrusions (attacks from outside the organization) and misuse (attacks from within the organization). The goal of this study is to develop a multistage ID technique for detecting flooding, blackhole, and gray-hole intrusions using Support Vector Machines (SVM). The SVM mechanism supports binary classification and separating data points into two classes. Hence, in this research SVM approach is used for classifying and detecting multiple attacks after breaking down the multiclassification problem into numerous binary classification problems. Keywords: Mobile Ad-hoc network, Support Vector Machine, On-demand Distance Vector, black hole, grayhole, flooding

ÖZ: Mobil Ad Hoc Ağlar (MANET'ler) son yıllarda birçok farklı alanda uygulanmaktadır. MANET'ler kötü niyetli davranışlara karşı oldukça savunmasız olsa da, tam güvenliğin sağlanması karmaşıktır. Önleme tekniklerinin yetersizliği nedeniyle, sistem etkinliğini izleyen ve izinsiz girişleri tespit eden Saldırı Tespit Sistemi (IDS) genellikle diğer güvenlik önlemleri ile birlikte kullanılmaktadır. Flooding, kara delik ve gri delik saldırıları gibi Hizmet Reddi (DoS) türü saldırılar, bilgisayar/ağ kaynaklarını meşru kullanıcılar için kullanılamaz hale getirmeyi amaçlayan akut ağ saldırı türleridir. İzinsiz Giriş Tespiti (ID), MANET gibi herhangi bir bilgisayar ağı için alarm mekanizması görevi gören bir güvenlik yönetim sistemidir. Bir ağa gelen güvenlik tehditlerini algılar ve ardından izinsiz girişe karşı gerekli önlemleri alması için bir varlığa bir alarm mesajı gönderir. Bir IDS, izinsiz girişler (kuruluş dışından saldırılar) ve kötüye kullanım (kuruluş içinden saldırılar) dahil olmak üzere olası güvenlik ihlallerini belirlemek için bir bilgisayar veya ağ içindeki çeşitli alanlardan bilgi toplar ve analiz eder. Bu araştırmanın amacı, flooding, kara delik ve gri delik saldırılarını tespit etmek için Destek Vektör Makinelerine (DVM) dayalı çok aşamalı bir kimlik mekanizması tasarlamaktır. SVM mekanizması, ikili sınıflandırmayı ve veri noktalarını iki sınıfa ayırmayı destekler. Bu nedenle, bu araştırmada, çoklu sınıflandırma problemini çok sayıda ikili sınıflandırma problemine böldükten sonra çoklu saldırıları sınıflandırmak ve tespit etmek için DVM yaklaşımı kullanılmıştır. Anahtar Kelimeler: Mobil Geçici ağ, Destek Vektör Makinesi, İsteğe Bağlı Mesafe Vektörü, kara delik, gri delik, flooding
Master of Technology in Information Technology. Institute of Graduate Studies and Research. Thesis (M.Tech.) - Eastern Mediterranean University, School of Computing and Technology, 2022. Supervisor: Prof. Dr. Ahmet Rizaner.
Keywords: School of Computing and Technology; Computer security; Computer networks--Security measures; Mobile Ad-hoc network; Support Vector Machine; On-demand Distance Vector; black hole; grayhole; flooding